2004
DOI: 10.1177/0898010104269313
|View full text |Cite
|
Sign up to set email alerts
|

Qigong as a Therapeutic Intervention With Older Adults

Abstract: The use of complementary therapies in the United States is growing. One complementary therapy that has received little attention in the nursing literature is Qigong. Qigong is the cornerstone of traditional Chinese medicine and consists of gentle flowing body movements, breathing, and quieting the mind. Qigong facilitates the movement of qi, the vital life energy, throughout the body, thereby enhancing health and healing disease. Preliminary research indicates that Qigong may be an effective complementary ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 22 publications
2
38
1
1
Order By: Relevance
“…Results cannot establish if a correlation also exists for exercisers older than 65 years as the present sample was middle-aged. Previous research has, however, indicated that qigong exercise is also suitable for people above the age of 65 (Jouper et al, 2006;Kemp, 2004). In contrast, very young healthy individuals may prefer more intense activities, and this may explain the lower exercise frequency in the younger participants in this study (cf.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Results cannot establish if a correlation also exists for exercisers older than 65 years as the present sample was middle-aged. Previous research has, however, indicated that qigong exercise is also suitable for people above the age of 65 (Jouper et al, 2006;Kemp, 2004). In contrast, very young healthy individuals may prefer more intense activities, and this may explain the lower exercise frequency in the younger participants in this study (cf.…”
Section: Discussioncontrasting
confidence: 66%
“…As suggested (Kemp, 2004), low-intensity mindbody activities such as qigong may be better suited to the needs and abilities of older adults. Our results show that age is positively associated with exercise sessions (r ¼ .40, po.001).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, some studies reported that qigong may also be linked to adverse events such as abnormal psychosomatic responses and even mental disorders. 1,12,15,18,26 Relative to those of standard drug treatments, these may be infrequent or even negligible. This systematic review focused on the effectiveness of qigong and thus adverse events were only assessed as reported in the included RCTs.…”
Section: Discussionmentioning
confidence: 95%
“…[21] Moreover, there is encouraging evidence which shows that ancient Chinese healing art, qigong, combined with movement exercises, meditation and controlled breathing, may lower BP significantly. [22]…”
Section: Hypertension and Cardiovascular Diseasementioning
confidence: 99%